Innovating Information Management System for Cow's Milk Distributor - Sutanto, Yusuf; Al Amin, Budi; Setyadi, Heribertus Ary (Universitas Bina Darma, 2023)
This study explores the recent advancements in cattle farming, focusing on the significant role of dairy farming in bolstering the economy, particularly in rural communities. It highlights how dairy farming enhances the economic value for farmers, with an emphasis on Banyuanyar Boyolali, where residents predominantly engage in this practice. The research underscores the profitability of selling cow's milk, noting the local milk prices, and aims to develop a web-based milk data management system. This system seeks to bring transparency and accessibility to milk production data, benefiting both farmers and collectors. Utilizing the Rapid Application Development (RAD) method, which involves minimal personnel, the study demonstrates how this web-based system streamlines data entry and access, facilitating better record-keeping and decision-making in dairy farming.